A nonsense mutation in the cathepsin K gene observed in a family with pycnodysostosis. - Johnson, M R; Polymeropoulos, M H; Vos, H L; Ortiz de Luna, R I; Francomano, C A (Genome Research, 1996)
Pycnodysostosis (MIM 265800) is a rare, autosomal recessive skeletal dysplasia characterized by short stature, wide cranial sutures, and increased bone density and fragility. Linkage analysis localized the disease gene to human chromosome 1q21, and subsequently the genetic interval was narrowed to between markers D1S2612 and D1S2345. Expressed sequence tagged markers corresponding to cathepsin K, a cysteine protease highly expressed in osteoclasts and thought to be important in bone resorption, were mapped previously in the candidate region. We have identified a cytosine to thymidine transition at nucleotide 862 (GenBank accession no. S79895) of the cathepsin K coding sequence in the DNA of an affected individual from a large, consanguinous Mexican family. This mutation results in an arginine to STOP alteration at amino acid 241, predicting premature termination of cathepsin K mRNA translation. All affected individuals in this family were homozygous for the mutation, suggesting that this alteration may lead to pycnodysostosis. Recognition of the role of cathepsin K in the etiology of pycnodysostosis should provide insights into the pathogenesis and treatment of other disorders of bone remodeling, including osteoporosis.
10.1101/gr.6.11.1050